Analysis of Indigenous Bacteria as Microplastic Degradation of Sediment in the Sea Waters of Dumai, Riau Province - Pakpahan, Deni; Yoswaty, Dessy; Nursyirwani, Nursyirwani (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
Nowdays Marine pollution resulted by microplastics is a global concern. Microplastic particles have the potential to cause damage to biota. One of solution to overcome the problem of marine pollution by microplastics by applying indigenous bacteria as microplastic degradation. This study was conducted to determine the type and ability of indigenous bacteria in sediments that are able to degrade microplastics. The research was conducted from October to December 2020. Sediment sampling was conducted in Dumai Sea Waters and sample analysis was conducted at the Marine Microbiology Laboratory, Faculty of Fisheries and Marine, Riau University. Indigenous bacteria from sediments were isolated in bacterial breeding media and then tested degradation capabilities on PET plastic samples. The result of the degradation test obtained ISL8 was able to degrade the mycoplastic with a percent degradation about 7%. Molecular test of ISL8 using PCR (Polymer chain reaction) 16S rRNA method and GenBank analysis is known that ISL8 is Bacillus sp.